Revisión de la investigación en motores de combustión interna en colombia (2019)
In this review we present the results of the exploration of the relevant research activities and topics developed in internal combustion engines by Colombian universities. The objective has been to determine what has been investigated, what theoretical, constructive, technological, operational and manufacturing foundations have been assumed by the research groups and researchers and, from there, to propose lines of research that complement and contribute. It was found that Colombia has competitive scientific capacity in: characterization of alternative fuels, diagnosis and prediction of combustion in ignition engines, modeling and prediction of perfor-mance of engines powered by ethanol-gasoline blends, characterization of emissions, modeling and experimentation in modes of ignition by compression of homogeneous load, design and construction of equipment for monitoring and diagnosis with non-intrusive techniques. In gene-ral, research has been driven both by environmental demands of the transport system and by the search for alternative fuel sources.